علامہ سید سلیمان ندوی ؒ کی علمی و تصنیفی خدمات کا جائزہ: Review of academic and literary services of Allama Syed Selman Nadvi - Dr Umme Salma (Al Manhal Research Journal, 2024)
Renowned writer, poet, researcher, critic, biographer, education expert and biographer Allama Syed Sulaiman Nadvi (1884 to 1953) Syed Sulaiman Nadvi was the dearest disciple and successor of Allama Shibli Nomani, he served the religion and nation and fulfilled the dreams of Allama Shibli. He used all his abilities to interpret the shame. You were a distinguished scholar of religion, a distinguished historian, a visionary thinker and a high-minded writer. It covers various aspects, Maulana was a great researcher, a great writer and a great scholar and commentator, In 1943, he wrote "Hayat Shibli" according to the teacher's will, in addition to "Sirat Hzrat Aisha (Razi Allah Anha)", the biography of the Prophet (peace be upon him) for children entitled” Rahmat Alam”, Khayyam, Sailing of the Arabs and the Arabs of India. Relationships, etc. are his famous and important works which he wrote during his stay at Darul Munsafin. Darul Munsafin was actually not the name of a building, but a corner of peace was prepared for the mental and intellectual training of Muslim youth during this era. There are hundreds of articles of Syed Sahib, among them, a collection of literary articles published by Darul Musafinin Azamgarh in three volumes (historical, scientific, religious) under the name of "Maqalat" Sulaiman was published in 1939 under the name "Naqosh Soleimani, "The first two volumes of Sirat-ul-Nabi ﷺ were completed during Allama Shibli's lifetime, but they could not get the opportunity to publish them. After his death, Syed Sahib published the first volume in 1918, the second volume in 1920, and the third volume in 1924. The fourth volume was published in 1932, the fifth volume in 1935 and the sixth volume in 1938.